SOCIETAL PERCEPTIONS ABOUT BEING A GOOD TEACHER IN LATVIA - Drelinga, Elga; Zariņa, Sandra; Iliško, Dzintra; Silova, Larisa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Teacher is one of the most responsible professions in the world because the teacher builds a sustainable society. There is an ongoing discussion about a professional competency of the teacher and changes in the requirements for teachers in the acquisition of knowledge, skills and attitudes required from teachers. There are numerous researches being carried out about the professional competency of teaching competency. The professional teaching standard that was ratified in 2004 is outdated but the new teaching standard is not designed yet because policy makers cannot come to an agreement about what a good teacher needs to know. For the changes to take place, the main aim of the study is to explore and to analyze societal opinion about the notion of a good teacher and competencies required for a good teacher. The research was carried out from May, 2016 until September with a participation of 160 respondents from different age groups. To ensure the validity of the study the authors used a questionnaire. Acquired data indicate that there exists a significant difference between the opinion expressed by the school age children and the opinion of adults. By describing the ideal of a good teacher pupils pay more attention to personal features of a teacher but adults pay closer attention to the skills and knowledge needed for a teacher.